Multifacility location problems on a sphere - Turgut Aykin; A. J. G. Babu (International Journal of Mathematics and Mathematical Sciences, 1987)
A unified approach to multisource location problems on a sphere is presented. Euclidean, squared Euclidean and the great circle distances are considered. An algorithm is formulated and its convergence properties are investigated.